Femur associated with the Deep Skull from the West Mouth of the Niah Caves (Sarawak, Malaysia). Issue 127 (February 2019) - Curnoe, Darren; Datan, Ipoi; Goh, Hsiao Mei; Sauffi, Mohammed S.
Abstract: The skeletal remains of Pleistocene anatomically modern humans are rare in island Southeast Asia. Moreover, continuing doubts over the dating of most of these finds has left the arrival time for the region's earliest inhabitants an open question. The unique biogeography of island Southeast Asia also raises questions about the physical and cultural adaptations of early anatomically modern humans, especially within the setting of rainforest inhabitation. Within this context the Deep Skull from the West Mouth of the Niah Caves continues to figure prominently owing to its relative completeness and the greater certainty surrounding its geological age. Recovered along with this partial cranium in 1958 were several postcranial bones including a partial femur which until now has received little attention. Here we provide a description and undertake a comparison of the Deep Skull femur finding it to be very small in all of its cross-sectional dimensions. We note a number of size and shape similarities to the femora of Indigenous Southeast Asians, especially Aeta people from the Philippines. We estimate its stature to have been roughly 145–146 cm and body mass around 35 kg, confirming similarities to Aeta females. Its extreme gracility indicated by low values for a range of biomechanical parameters taken midshaft meets expectations for a very small (female) Paleolithic East Asian. Interestingly, the second moment of area about the mediolateral axis is enlarged relative to the second moment of area about the anteroposterior axis, which could potentially signal a difference in activity levels or lifestyle compared with other Paleolithic femora. However, it might also be the result of sexual dimorphism in these parameters as well as possibly reflecting changes associated with aging.